2011
DOI: 10.1007/s10337-011-2030-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Ionic Liquid-Gas Partition Coefficients for Residual Solvents by HS-GC

Abstract: The aim of this study was to establish a method to determine the partition coefficients of residual solvents (eight aliphatic alcohols) between three ionic liquid and gas phases by headspace gas chromatography (HS-GC). In this article, a modeling study was carried out using statistical analysis, and a general model was established to predict the ionic liquid-gas partition coefficients (K) for these solvents. Factors that affect the logK, including parameters of physical properties of these solvents, such as T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…ILs, as a group of novel solvents, are used as ideal matrix media due to their inherent properties, including negligible vapor pressure, high thermal stability, and excellent solubility. In our group, we have applied ILs as headspace matrix media for analyzing residuals in pharmaceuticals [20,21]. In our current study, more volatile components, including components with high-boiling points and low content, were detected using only 100 mg of sample by [Bmim][BF 4 ] based HS-GC-MS.…”
Section: Resultsmentioning
confidence: 89%
“…ILs, as a group of novel solvents, are used as ideal matrix media due to their inherent properties, including negligible vapor pressure, high thermal stability, and excellent solubility. In our group, we have applied ILs as headspace matrix media for analyzing residuals in pharmaceuticals [20,21]. In our current study, more volatile components, including components with high-boiling points and low content, were detected using only 100 mg of sample by [Bmim][BF 4 ] based HS-GC-MS.…”
Section: Resultsmentioning
confidence: 89%
“…As commented above, the extremely low vapor pressure of ILs promoted their use as matrix media in green HS-GC-MS procedures for analysis of RSs in the pharmaceutical field [21][22][23][24][25][26]. As an example, Laus et al [21] showed the utility of using 1-N-butyl-3-methylimidazolium dimethyl phosphate ([BMIM] [DMP]) as solvent for the successful HS-GC-MS analysis of DMSO, N-methylpyrrolidone, sulfolane, tetralin, and ethylene glycol in a realistic matrix of commonly-used excipients (carboxymethylcellulose, magnesium stearate, guar flour, and corn starch) in pharmaceutical products.…”
Section: Applicationsmentioning
confidence: 99%